Costs in Pituitary Surgery: Racial, Socioeconomic, and Hospital Factors - Parasher, Arjun K.; Workman, Alan D.; Kidwai, Sarah M.; Goljo, Erden; Signore, Anthony Del; Iloreta, Alfred M.; Genden, Eric M.; Shrivastava, Raj; Navathe, Amol; Govindaraj, Satish (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objective To investigate the influence of patient demographic factors and hospital factors on cost and length of stay in patients undergoing pituitary surgery.Design/Setting A retrospective cross-sectional study of the 2008 to 2012 Nationwide/National Inpatient Sample.Participants Patient demographics and hospital characteristics for patients undergoing pituitary surgery were compared between white, black, and Hispanic patients.Main Outcome Measures Variables associated with increased cost and increased length of hospital stay were ascertained and compared against each racial and ethnic group via multiple linear regression analysis.Results Of 8,812 patients who underwent pituitary surgery, 5,924 (67.2%) patients were white, 1,590 (18.0%) were black, and 1,296 (14.7%) were Hispanic. Patient variables found to be significantly different between racial groups via univariate analysis were age, chronic conditions, gender, income, and primary payer. Hospital variables found to be significantly different were location/teaching status, region, and ownership. Hospitalization cost was significantly lower for whites (−$3,082, 95% confidence interval [CI] −$3,961 to −$2,202) and significantly higher for both blacks ($1,889, 95% CI $842–$2,937) and Hispanics ($2,997, 95% CI $1,842–$4,152). Length of hospital stay was also significantly lower in whites (−1.01, 95% CI −1.31 to −0.72) and significantly higher for both blacks (0.65, 95% CI 0.30 to 1.00) and Hispanics (0.96, 95% CI 0.57–1.35).Conclusions Racial and ethnic factors contribute to differences in hospital utilization and cost for patients undergoing pituitary surgery. Further investigations are necessary to uncover the sources of these disparities in an effort to provide safer and more affordable care to all patients.
Keywords: pituitary surgery; skull base; health care disparities; cost; outcomes/cost-effectiveness